Optical domain service differentiation using spectral-amplitude-coding - S.B., Ahmad Anas; Mohamad Khazani, Abdullah; M., Mokhtar; Syed Alwee Aljunid, Syed Junid; S.D., Walker (Elsevier Inc., 2009)
Link to publisher's homepages at http://www.elsevier.com/wps/find/journal_browse.cws_home